Removal performance of pollutants from industrial wastewater using scirpus grossus - Puvithra, Mathuraveeran (2019)
In this era of complex and modern technology, pollution is the biggest fear in world. Air pollution, water pollution, soil pollution and many more have become a severe problem to the world to cope with. Water pollution is a serious problem in Malaysia and impact negatively on the sustainability of water resources. Phytoremediation is the best treatment for the contaminant wastewater. This treatment is cheap, easy to maintenance and economical. Besides that, phytoremediation is an emerging technology that should be considered for the remediation of contaminated sites because of its aesthetic advantages and long-term applicability. The objectives of this study was to identify the label of pollutant contains in industrial wastewater for baseline information and to determine the effectiveness of phytoremediation plant (scirpus grossus) to remove the pollutant contains in wastewater. Scirpus Grossus (club-rush) was used to find out removal capacity that contain in industrial wastewater. The experiment was run for one month by identify the in-situ and ex-situ parameters at Environmental Laboratory of Universiti Malaysia Pahang. The wastewater was collected from the study area and was analysed to collect the water quality data. The experiment was carried out for one-month duration with average of 3 measurements for each percentage. The parameters that was tested were pH, dissolved oxygen (DO), temperature, turbidity, Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), ammoniacal nitrogen, cadmium (Cd), zinc (Zn) and iron (Fe). Based on the experiment, the removal capacity was higher when the 50% dilution of the dilution, which was for turbidity, BOD, COD, TSS, ammoniacal nitrogen and Zn were 69.33%, 69.92%, 81.48%, 64.63%, 68.36%, 64.29% respectively. Cd was 70.59% for 70% dilution while Fe was 81.94% for 100% without dilution. Scirpus Grossus was not effective without dilution. The removal capacity was higher when the 50% dilution of the wastewater after one month treatment.